Sedimentary vanadium isotope signatures in low oxygen marine conditions. (1st September 2020) - Wu, Fei; Owens, Jeremy D.; Scholz, Florian; Huang, Linqing; Li, Siqi; Riedinger, Natascha; Peterson, Larry C.; German, Christopher R.; Nielsen, Sune G.
Abstract: It has been hypothesized that vanadium (V) isotopes have the potential to track sedimentary redox conditions due to multiple valence states occurring in nature, which might induce variable V isotope fractionation as a function of sedimentary redox state. These characteristica could make V isotopes a useful paleo-redox proxy. However, in order to understand the mechanisms driving V isotope fractionation, it is crucial to build a framework for the depositional and post-depositional controls on sedimentary V isotope records from a diverse set of sedimentary environments. This study, for the first time, investigates the V isotope variations of modern marine sediments deposited under a range of redox environments. Our results document that changes in local redox conditions impart a significant isotopic fractionation from seawater as recorded in the local sedimentary V isotopic signature. Importantly, there is a significant difference between the V isotope composition of sediments deposited in the open ocean setting with oxygen-deficient bottom waters compared to less reducing environments, whereby oxic sediments (benthic oxygen contents > 10 μΜ) exhibit Δoxic = −1.1 ± 0.3‰ and anoxic sediments exhibit Δanoxic = −0.7 ± 0.2‰. Combined with previous studies on seawater particulate and sediment pore fluid analysis, our results indicate that V is mainly delivered and enriched in anoxic sediments through settling particulates. Authigenic V isotope compositions in marine sediments are likely controlled by isotope fractionation between V species bound to particulates and dissolved in seawater, which likely varies with the speciation and adsorption properties of V that are strongly controlled by local redox conditions. In addition, the euxinic Cariaco Basin sediments exhibit distinctive Δeuxinic = −0.4 ± 0.2‰, which is likely influenced by the relationship between the seawater V removal rate and the seawater renewal rate. Our results highlight the direct link between authigenic marine sedimentary V isotope compositions and the overlying local redox conditions. This investigation of V isotopes in modern marine environments provides an initial framework for the utilization of V isotopes to reconstruct ancient redox fluctuations, which has the potential to track subtle redox variations of local oxygen-deficient to low oxygen environments.